Privatización e iniciativa emprendedora: El efecto del entorno competitivo - Zulima Fernández Rodríguez; A. M. Romero Martínez; E. Vázquez Inchausti (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
This work analyses the changes in entrepreneurship of state-owned enterprises (SOEs) after privatization, including sales of firms and deregulation. A sample of Spanish firms privatized between 1985 and 2000 shows that these companies have experienced a significant increase in entrepreneurship. After privatization their level of product, process and organizational innovation is higher; they also develop new businesses at domestic level, reinforce their international activity and embark on strategic renewal processes. In addition, we have found that these changes become more drastic when competition is high.
Keywords: 330; privatization; entrepreneurship and competition